East Timor (Timor-Leste) - Jerónimo, Patrícia (2018)
Timorese citizenship was born with the new independent state, on 20 May 2002. The Constitution of the Democratic Republic of Timor-Leste (Constituição da República Democrática de Timor-Leste), which entered into force on that same day, set the criteria for the attribution of Timorese citizenship by birth (cidadania originária) and referred to ordinary legislation the definition of the rules on acquisition, loss, reacquisition, registration and proof of Timorese citizenship (Article 3, under the heading ‘citizenship’). Much like the rest of the constitutional text, Article 3 reflects the combined influences of the Mozambican Constitution of 1990 and of the Portuguese Constitution of 1976. The first is reflected in the Constituent Assembly’s option for setting substantive criteria for the attribution of citizenship, while the second is evidenced by its option for referring the bulk of the citizenship regime to ordinary legislation. The combination is not without difficulties. Article 3 of the Timorese Constitution adopts the traditional jus soli and jus sanguinis principles for the attribution of citizenship by birth. Both principles are enunciated in very broad terms, making access to Timorese citizenship by birth remarkably easy. This may be explained by the fact that Timor-Leste is a small and poor country with a vast diaspora, but later legal developments, i.e. the adoption of the 2002 Nationality Act and of the 2004 Nationality Regulation, suggest that the Constituent Assembly might have come across as more inclusive than what was actually intended. The attempts made by the National Parliament and by the Government to introduce restrictions in the access to Timorese citizenship by birth lack a constitutional mandate and should be deemed unconstitutional. The issue, however, has not yet reached the Timorese courts and seems to be absent from academic and political debates in the country. The chapter provides historical background to the current citizenship regime in Timor-Leste, covering membership criteria under Portuguese colonial rule, Indonesian military occupation and the United Nations Transitional Administration (UNTAET). It makes a critical assessment of the current citizenship regime, covering modes of attribution, acquisition, loss and reacquisition of Timorese citizenship, as well as the rights of Timorese citizens by origin and by naturalisation.